Ecologically relevant phosphorus pools in soils and their dynamics: The story so far - Weihrauch, Christoph; Opp, Christian (Geoderma, 2018)
There has been much soil phosphorus (P) research in the last decades, but few basic publications exist summarizing the current state of knowledge on ecologically relevant P forms and their reactions in soils. The present paper aims at giving such a literature overview. The major P forms occurring in soils are presented. Organic P results from biogenic processes when organisms take up P from the soil. After their death, this P is returned into the soil and has to be mineralized before the next uptake. Mineralization intensity depends on the concentration of dissolved inorganic P in the soil solution. Only this soil P fraction can be taken up by plants and microorganisms and enter the food chain. Thus, it is critical for ecosystem nutrition. Dissolved P is highly affine for binding to the soil matrix and strives for equilibrium with bonded P forms. On the one hand, there is sorbed P, regularly forming quickly and being easily exchanged back into the soil solution. Sorbed P strongly depends on which and how many sorption sites a soil offers. Some of these sites are not easily accessible. Thus, P needs time to be sorbed there and is slightly soluble afterwards. This fraction is termed “occluded P”. It is considered fixed and not bioavailable for long times. On the other hand, there is mineral P, resulting from the precipitation of P anions and metal cations when the soil solution is oversaturated with these ions. The stability of mineral P depends on its degree of order, amorphous phases being less stable than highly crystalline minerals. Organic, sorbed and mineral P are tightly interconnected with dissolved P and strive for equilibrium with it. Due to changes in temperature, precipitation and vegetation/edaphic patterns such equilibrium is hardly attained and soil P reactions must dynamically adjust to present conditions. [Display omitted] •The major soil P fractions and their reactions are presented.•Organic and inorganic P forms (dissolved, sorbed, occluded, mineral) are characterized.•A conceptual model illustrating interconnections between major P fractions is proposed.•Dissolved P is the most dynamic and mobile fraction and determines reactions of the other P pools.•Changes in temperature, precipitation and vegetation/edaphic patterns trigger P reactions.